2016
DOI: 10.18052/www.scipress.com/ilns.59.29
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Quality in Woody Plants in the City Parks of Dnipro, Ukraine

Abstract: Abstract. This research was conducted to study pollen quality in woody plants in the city parks of Dnipro, which are located at various distances from the sources of anthropogenic pollution. It has been revealed that sterile pollen in its greatest abundance was present in plant species in the Park of Memory and Reconciliation and Molodyozhny park, as both are situated within the range of emission transfer from the Western Industrial Complex, while the least abundant sterile pollen was detected in the park name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Cuinica et al (2015) indicated that even at low levels of pollutants below the standard level of safety for human health, pollen viability decreased to 25%. The total amount of teratomorphic pollen increased with increasing concentration of air pollutants and reached 11.1% (Ivanchenko and Bessonova 2016;Petrushkevуch and Korshуkov 2020). The percentage of natural polymorphism of pollen grains in plants under favourable conditions usually does not exceed 5%-10% and rarely exceeds 20% (Dzyuba 2006;Ivanchenko and Bessonova 2016).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Cuinica et al (2015) indicated that even at low levels of pollutants below the standard level of safety for human health, pollen viability decreased to 25%. The total amount of teratomorphic pollen increased with increasing concentration of air pollutants and reached 11.1% (Ivanchenko and Bessonova 2016;Petrushkevуch and Korshуkov 2020). The percentage of natural polymorphism of pollen grains in plants under favourable conditions usually does not exceed 5%-10% and rarely exceeds 20% (Dzyuba 2006;Ivanchenko and Bessonova 2016).…”
Section: Discussionmentioning
confidence: 98%
“…The total amount of teratomorphic pollen increased with increasing concentration of air pollutants and reached 11.1% (Ivanchenko and Bessonova 2016;Petrushkevуch and Korshуkov 2020). The percentage of natural polymorphism of pollen grains in plants under favourable conditions usually does not exceed 5%-10% and rarely exceeds 20% (Dzyuba 2006;Ivanchenko and Bessonova 2016). In our studies, the amount of teratomorphic pollen reached 41.4% and increased with increasing concentration of contaminants (r = 0.76).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations